Optimizing Coil Raw Material Inventory for Pipe Manufacturing Using EOQ, Reorder Point and Safety Stock at PT. XYZ - Kemal Darma Nazidan; Isna Nugraha (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Steel coil raw material inventory plays an important role in ensuring the smooth production process. PT XYZ faces inventory instability, both in the form of shortages and excess stock, which causes production constraints and increases storage costs. This study aims to determine the most accurate forecasting method, calculate the economic order quantity, determine the reorder point, and determine the amount of safety stock so that inventory control is more optimal each month. The methods used include forecasting with Economic Order Quantity to predict raw material needs and calculations. Reorder Point and Safety Stock to determine the order quantity, optimal inventory, and the minimum point of raw materials for restocking. Based on the analysis results, the pattern of steel coil usage shows a seasonal trend. The forecasting results using the Weighted Moving Average method provide the smallest error rate with an MSE value of 5,856,347.80 and a MAD of 2,175.80. Through the application of the EOQ method, the optimal order quantity is 3039 tons, a reorder point of 3162 tons, and a safety stock value of 4,572.447 tons. The conclusion obtained from this study is that the forecasting and EOQ methods are able to increase the efficiency of inventory control and minimize the risk of shortages of coil raw materials every month at PT XYZ.